2005
DOI: 10.1093/hmg/ddi230
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of genome scans of age-related macular degeneration

Abstract: A genetic contribution to the development of age-related macular degeneration (AMD) is well established. Several genome-wide linkage studies have identified a number of putative susceptibility loci for AMD but only a few of these regions have been replicated in independent studies. Here, we perform a meta-analysis of six AMD genome screens using the genome-scan meta-analysis method, which allows linkage results from several studies to be combined, providing greater power to identify regions that show only weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
120
0
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(130 citation statements)
references
References 55 publications
5
120
0
5
Order By: Relevance
“…Previously several groups reported that the AMD 10q locus has been associated with both GA and wet AMD phenotypes. [13][14][15][16] Our expanded findings are in agreement with these findings.…”
Section: Discussionsupporting
confidence: 91%
“…Previously several groups reported that the AMD 10q locus has been associated with both GA and wet AMD phenotypes. [13][14][15][16] Our expanded findings are in agreement with these findings.…”
Section: Discussionsupporting
confidence: 91%
“…Genome-wide linkage analyses of extended families with AMD have identified a number of chromosomal loci that are linked to AMD. The most consistent of these occurs at chromosome 1q31 (210). Between 15% and 40% of multiplex AMD families segregated with a disease gene in the 1q31 region (204).…”
Section: Molecular Genetics Of Amd and Disease Associationsmentioning
confidence: 99%
“…The chromosome 1q32 region has long been considered to possess a susceptibility locus for AMD [29]. Edwards, Haines, Klein, Hageman and their colleagues [30][31][32][33] recently reported in four independent studies that the tyrosine to histidine at position 402 (Y402H) SNP in the CFH gene in the 1q32 region increases the risk of AMD.…”
Section: Complement Components and Complement Regulatory Proteins In mentioning
confidence: 99%